A MUNDIALIZAÇÃO E A AUTONOMIA RELATIVA DO DIREITO NA DEFINIÇÃO DE MODELOS DE DESENVOLVIMENTO NACIONAIS: O caso da organização jurídico-institucional da navegação marítima brasileira atual. - Caldenhof, Peter Loeb (2015)
This dissertation studies the relations between the socioeconomic base and the political-juridical superstructure, with the demonstration that they form a dialectic totality, but keeping the relative autonomy of its parts. The text shows the specific nature of Law as an important part of the superstructure and its role in the definition of national development models within the process of mundialization. The relative autonomy of Law is demonstrated in theoretical and historical-concrete terms, first, by showing that there is no automatic determination of Law by the socioeconomic structure and, second, with the evidence of the political and juridical constitution of the material base itself. These elements of the relative autonomy are explained by the political and juridical characteristics of the state, Law, the international system and the mundialization process as something that is deliberately produced by the different actors in conflict within the domestic and international superstructures. Parting from this point of view of critical institutionalism, the relations between Law and Economics are demonstrated and analyzed in the case study of the current juridical-institutional organization of the shipping industry in Brazil and its effects in terms of development for the shipping branch and the economy as a whole. The dissertation shows that the current model is insufficient for the consolidation of an autonomous national shipping industry, with the consequent negative impacts on the systemic competitiveness of the Brazilian economy, its national accounts, the national accumulation of capital and the development of correlated economic sectors, such as the shipbuilding industry.